Do cortisol affects the brain electrical activity (EEG powers)? - Namrata Upadhayay; Rita Khadka; Nirmal Baral; Prahlad Karki; Bishnu Hari Paudel (Al Ameen Medical College, 2022)
Background: Glucocorticoids at very low/high levels are detrimental for memory performance. But how electroencephalogram (EEG) activity correlates with the cortisol in high and low efficient brains are still controversial. Objective: To find the association of cortisol with EEG powers in high and low cognitive brains at the time of examination preparation. Method: The EEG was recorded in an eye-closed state for 5-minutes in high (n-59) and low (n-24) cognitive individuals. Their salivary cortisol was estimated and correlated with the EEG activity by Spearman correlation test (p<0.05). The cortisol level between two groups was compared by Mann-Whitney U test. Result: Cortisol (ng/ml) was high in low cognitive group (1.36) than to the other group (1.32).There was a negative association of cortisol with EEG powers (r= -0.41 to -0.5) in central (beta, alpha2), frontal (alpha2) and left-temporal (alpha2) regions of the low cognitive brains. In high cognitive brains, cortisol was negatively associated with beta activity in right-temporal (r=-0.27) but positively associated with theta activity in mid-frontal (r=0.33) brain area. Conclusion: The less efficient brain has high cortisol level during preparation for their examination. This might have decreased the alpha2 activity in them that will impair the processing of long term memory. However, these individuals seem to manage the examination stress by decreasing the firing of the beta activity. Conversely, in the high cognitive brain, the rise in cortisol level seemed to increase the mid-frontal theta activity that might improve the attention and encoding of the information in these individuals.